(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
This study examines how teachers and students interact in online learning, especially after the shift to distance education during COVID-19. A survey of 15 people – 2 teachers and 13 students – focused on feedback, engagement, and emotional support. The results show that while personalized feedback and emotional support are crucial for keeping students engaged, they’re often inconsistent. Common challenges include technical issues and the lack of in-person interaction. To improve online learning, the study suggests more frequent feedback, creative teaching methods, and fostering a stronger sense of community.